MITIGASI BENCANA DALAM LONTAR ROGHA SANGHARA BHUMI: Kajian Religius Saintifik - Joniarta, Made; Girinata, I Made; Wiguna, I Made Arsa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
In the principle of socio-ecology, the existence of various natural phenomena is a dynamic form that occurs in the spiritual and empirical corridor of humans in knowing the substance of the relationship of life between various dimensions, both physical and metaphysical. Hinduism in Bali has inherited a supply of fundamental knowledge regarding the context of disasters, which in various ritual practices carried out have the main purpose of harmonizing life between humans, God, and nature. Regarding this statement, knowledge about disasters and their mitigation is summarized in one of the tattwa texts called Lontar Rogha Sanghara Bhumi.This research is a qualitative research. In order to produce valid and credible research, this research uses two types of theoretical foundations to test the truth of the data obtained during the research. In this case, the eco-semiotic theory is used to analyze the signs of disaster conveyed by Lontar Rogha Sanghara Bhumi, while the Tri Hita Karana Theology theory is used to analyze the mitigation carried out for disaster management according to Lontar Rogha Sanghara Bhumi, and in the data analysis technique, content analysis is used so that this research can be presented descriptively.The findings produced in this study are the signs that appear before and are felt before the earthquake disaster occurs. The earthquakes in each sasih are believed to have different values ​​and impacts so that the type of earthquake that has a destructive impact on nature and the type of earthquake that is believed to be a sign that the universe has been given a gift by God can be identified. Another finding is that the mitigation that should be carried out to overcome the disaster is by carrying out various tawur rituals such as Pancawalikrama and Labuh Gentuh to overcome disasters that occur periodically, while the nangluk merana, prayascitta, and guru piduka ceremonies are used to overcome disasters that occur incidentally.